The genus Hybocodon (Cnidaria, Hydrozoa) in the southwestern Atlantic Ocean, with a revision of the species recorded from the area - Rodriguez, Carolina S.; Miranda, Thaís P.; Marques, Antonio C.; Mianzan, Hermes; Genzano, Gabriel (Zootaxa, 2012)
The genus Hybocodon includes seven species, two of which (H. prolifer and H. unicus) have been recorded in the south-western Atlantic. These reports were based on the medusa stage and only a few diagnostic characters were described, ren-dering some of these records rather doubtful. Additionally, H. prolifer has a boreal distribution, suggesting that the reportsof this species from the southern hemisphere could correspond to other Hybocodon species. Recently, we sampled benthicand planktonic specimens of Hybocodon in the southwestern Atlantic and two species were identified: polyps andmedusae of Hybocodon chilensis Hartlaub, 1905, and medusae of Hybocodon unicus (Browne, 1902). These samples al-lowed us to review and discuss the geographical distribution and validity of previous records of Hybocodon species forthis area. We conclude that H. chilensis and H. unicus are the only Hybocodon species presently known for the southwestern Atlantic Ocean.